Contamination of Escherichia coli Drinking Water Refills on Drinking Water Depots in Malang City - Kusmawati, Wiwik; Rahayu, Lia (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Data from the Malang City Health Office shows the increasing number of refill drinking water depots in the city of Malang until 2013 there were 163 drinking water depots scattered in each Malang Subdistrict. The purpose of this study was to determine the contamination of Escherichia coli refill drinking water in drinking water depots in Malang. The samples taken were 20 refill drinking water depots in Malang. Sampling is done by simple random sampling. Escherichia coli examination using the Most Probable Number Test. Of the 20 samples tested, 2 samples met the requirements of drinking water quality according to PERMENKES and 18 other samples containing the number of coliform bacteria exceeding the maximum limit of 0 per 100 ml of water. There were Escherichia coli in 10 samples while 8 other samples contained other coliform bacteria.